Keseimbangan produksi dan konsumsi dalam perspektif islam dan relevansinya terhadap ekonomi modern - Khotimah, Siti (Maliki Interdisciplinary Journal, 2025)
Production and consumption activities are crucial components in the economy. In Islamic teachings, contained in the Qur’an and Hadith, there are instructions for people to always maintain balance in the utilization of resources, the manufacture of goods, and the expenditure of wealth. The application of this balance value is very important so that there is no waste or shortage that can have a negative impact on society and the environment. This article aims to describe how Islam establishes the principle of balance in production and consumption, and explains how to apply it in managing the economy today. The writing approach is carried out by analyzing sources such as the Qur’an, Hadith, tafsir literature, and current management theories. The findings from this discussion indicate that the application of the principle of balance can help companies regulate production according to market demand, avoid overstock, and educate the public to shop wisely. Thus, Islamic values serve to support a fair, efficient, and sustainable economy in the contemporary era.